(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study focuses on India’s anti-imperialist movement while examining women’s national perspectives and regional narratives around freedom fights. Traditionally, the history of the Indian liberation movement has exalted "great leaders," so obscuring the roles played by the stratified masses and local fights. In response to this imbalance, the subaltern school of history was formed in the 1970s, emphasizing local movements and oppressed voices within the larger national narrative. In addition, the study examines the worldwide context of freedom by referencing the evaluations of political rights and civil freedoms conducted by Freedom House. It aims to comprehend how women participated in and influenced the nationalist movement by examining significant moments in India’s freedom struggle, such as the first war of independence, the Swadeshi Movement, and the Quit India Movement, along with the contributions of female leaders like Sarojini Naidu, Rani Laxmi Bai, and Kamaladevi Chattopadhyay. The objective of this research is to enhance comprehension of the crucial era in Indian history by presenting the varied viewpoints and experiences that were part of the country’s freedom movement.